RARE CASE OF PINEAL GERMINOMA WITH ARGININE VASOPRESSIN DEFICIENCY - Barakath, Mohamad Firdaus; Sambamoorthy, Vijayrama Rao; Rahim, Anilah Abdul; Rahmatullah, Ijaz Hallaj (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKCGROUND Pineal tumour is an uncommon type of brain tumour in Malaysia, with low incidence rate of 2.1% based on a demographic study done in 1 of the states in Peninsular Malaysia. On the other hand, germinoma is a common cause of intracranial tumor leading to arginine vasopressin deficiency (AVP-D). In a literature review, 82% of 95 patients were diagnosed with AVP-D. CASE We report a case of a 22-year-old Malay male, who was diagnosed with pineal gland tumour complicated with obstructive hydrocephalus. He underwent endoscopic biopsy of pineal region tumor and right ventriculoperitoneal shunt insertion in January 2024. Two days after his surgical intervention, he developed an episode of polyuria with urine output more 5 ml/kg/hr for consecutive hours in the ward without any accompanying thirst. Investigations showed high serum osmolarity of 294 mOsm/kg (NR: 271-286 mOsm/kg) with inappropriately low urine osmolarity of 161 mOsm/kg (NR: 300-900 mOsm/ kg). He was diagnosed with AVP-D and responded well to intravenous desmopression (DDAVP), a vasopressin synthetic analogue, with reduction in urine volume and passing more concentrated urine. Over the next few days, he started to develop more episodes of polyuria, requiring regular dosing of desmopressin. The tissue histopathology of the pineal gland revealed germ cell tumour consistent with germinoma. CONCLUSION AVP-D is a known complication of intracranial germ cell tumour. Our case report shows that AVP-D may also happen as a consequence of neurosurgical intervention. Careful clinical and biochemical postoperative monitoring remains essential to correctly diagnose and manage AVP-D following neurosurgery intervention.